Analisis Penanganan dan Kendala Petugas Load Control dalam Membuat Weight And Balance pada Pesawat Malaysia Airlines Boeing 737-800 Di PT JAS Bandar Udara Internasional Soekarno Hatta Cengkareng - Hairunisa Hairunisa; Fauzia Fahmi Yuniarti Nasution (Nian Tana Sikka : Jurnal ilmiah Mahasiswa, 2024)
Load Control is a unit responsible for receiving and analyzing aircraft data and locals from various sources to ensure optimal aircraft balance with reference to safety and economical operation aspects. The purpose of this study is to understand the handling, challenges, and efforts of Load Control officers in creating the Weight and Balance for Malaysia Airlines Boeing 737-800 at PT JAS Soekarno Hatta Internasional Airport. The research method used in this study is descriptive qualitative, utilizing primary data (interviews and observations) and secondary data (documentation) in the from of Standard Operating Prosedures (SOP). Data analysis is conducted, data reduction, data presentation, and conclusions. The result of the study at Soekarno Hatta International Airport, Cengkareng, show that Load Control officers have carried out the Weight and Balance for Malaysia Airlines Boeing 737-800 in accordance with the specified Standard Operating Prosedures (SOP), especially in handling cargo that requires special attention. The challenges faced in creating Weight and Balance include ineffective communication between units, system disruptions or system down, and overload issues that can affect flight On The Performance. Efforts to address these challenges by Load Control officers include adhering to Standard Operating Prosedures (SOP), improving communication, and coordinating with various related parties to achieve On The Performance..